From the foundations to the crenellations essays on temple building in the Ancient Near East and Hebrew Bible - Boda, Mark J. 1962-; Novotny, Jamie (Münster Ugarit-Verl., 2010)
Literaturverz. S. [517] - 561
pt. 4: Appendices.Appendix 1:Selected Aramaic, Akkadian, Hittite, Phoenician, Persian, Sumerian, and Ugaritic sources ; Appendix 2:Catalogue of Elamite sources ; Appendix 3:Hebrew Bible passages connected to Ancient Near Eastern (re)construction rituals and texts with select bibliography.
Literaturverz. S. [517] - 561
Archivierung prüfen
Keywords: Temple of Jerusalem (Jerusalem); Bible -- History of Biblical events; Temples -- Middle East -- Design and construction; Middle East -- Antiquities; Palestine -- Antiquities; Aufsatzsammlung